INCREASING THE EFFECTIVENESS OF EDUCATION THROUGH TEACHING THE PHYSICAL BASIS OF MILITARY APPLIED TASKS IN THE TRAINING OF MILITARY SPECIALISTS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article highlights the didactic possibilities of teaching the physical foundations of military-applied tasks, taking into account the professional focus and features of ensuring the effectiveness of education.